Difference of Non Profilling Ultrafiltration Settings with One Profiling Ultrafiltration on Reduction of Intradialistic Blood Pressure - Rimna Rita; Riyan Saputra; Ratih Andela; Sunarti Sunarti (Jurnal Penelitian Perawat Profesional, 2020)
Hemodialysis is a process of withdrawing a substance in the body and replacing it with substances that are new substitutes for kidney function therapy. The hemodialysis process uses two stages of ultrafiltration, namely non-profiling ultrafiltration and one-profile ultrafiltration. The general objective of the study was to determine the differences between the regulation of Non-Profilling Ultrafiltration and Ultrafiltration Profilling One Against the Reduction of Blood Pressure Intradialysis in the Hemodialysis Installation at Royal Prima General Hospital in 2019. This type of research is quasi-experimental with a control group. The population in this study were patients undergoing hemodialysis at RSU Royal Prima, the number of samples in this study were 55 respondents, with a total sampling. The results of the non-profiling ultrafiltration group with majority blood pressure fell by 46 people (83.6%) minority rose by 9 people (16.4%). The profiling ultrafiltration group with majority blood pressure fell by 34 people (61.8%) normal minority by 2 people (3.6%). The value of sig (2-tailed) = 0.077 and α = 0.05, then 0.077> 0.05 then Ho is accepted Ha is rejected, meaning that there is no difference between withdrawal not in profile and withdrawal using profile one that influences the decrease in blood pressure in the unit hemodialysis Royal Prima Medan Hospital in 2019.